Evaluation of awareness toward various treatment options and maintenance practices among removable partial and complete denture patients in Western Maharashtra - A questionnaire-based study - Arti Gachake; Ajay Sabane; Pankaj Kadam; Abhijit Patil; Meenal Tepan; Bhagyashri Kalsekar; Anushka Puri (Wolters Kluwer Medknow Publications, 2024)
Introduction: Researchers must concentrate their focus on whether patients understand various treatment options available among removable complete and partial denture patients and whether they are aware of the maintenance protocol of the prosthesis. Materials and Methods: All the patients who completed removable partial or complete denture treatment in a period of 6 months were included in the study. Collected data were statistically analyzed using Chi-square test at a significance level of P < 0.05. Results: Awareness needs to be increased regarding the treatment options available for removable complete and partial denture treatment causes because many subjects in this study were only aware of the removable partial denture and complete denture treatment for missing teeth and not the other options, especially among individuals in the lower socioeconomic group. Conclusion: The findings indicate that awareness needs to be increased regarding the functions of prostheses such as esthetics and phonetics because many subjects in this study were only aware of the masticatory function performed by prosthesis.